In silico profiling of diaza- and tetraazabicyclononan-9-ones as novel nicotinic acetylcholine receptor ligands (International Journal of Biology and Chemistry, 2026)
Nicotinic acetylcholine receptors (nAChRs) are promising therapeutic targets for treating cognitive disorders and nicotine addiction. This study aimed to identify a novel nAChR ligand from a series of 8 newly designed diaza- and tetraazabicyclononan-9-ones using a comprehensive in silico approach. The biological activity spectrum was predicted using the PASS program, revealing a high potential for nAChR antagonism and other neurotropic activities. Pharmacokinetic and drug-likeness properties were assessed with SwissADME, indicating favorable profiles for most compounds. Molecular docking into the orthosteric site of the human α3β4-nAChR (PDB ID: 6PV7) and α4β2-nAChR (PDB ID: 5KXI) was successfully performed for six derivatives. Among them, compound 1 demonstrated a superior calculated JAMDA Score (-2.60), outperforming the native ligand, nicotine (JAMDA Score: -1.99). Analysis of the binding pose revealed that its superior predicted affinity stems from a network of specific hydrogen bonds with key residues (Tyr93, Ser148, Ser150) and an interaction with the backbone of Trp149 in the orthosteric site. Thus, the integrated in silico strategy identified compound 1 as a potent putative nAChR ligand, warranting its priority for further experimental evaluation.Keywords: nicotinic acetylcholine receptors, molecular docking, in silico screening, bicyclic nitrogen heterocycles, drug design.